2011
DOI: 10.1007/s10851-011-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Low-Pass Filters for Image Processing with Inverse Laplacian Models

Abstract: A novel signal processing-oriented approach to solving problems involving inverse Laplacians is introduced. The Monogenic Signal is a powerful method of computing the phase of discrete signals in image data, however it is typically used with band-pass filters in the capacity of a feature detector. Substituting low-pass filters allows the Monogenic Signal to produce approximate solutions to the inverse Laplacian, with the added benefit of tunability and the generation of three equivariant properties (namely loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We have empirically showed that the pixelwise cell-background classification yields considerably better results when the local phase as obtained in [7] is used instead of the defocused image. Nevertheless, the defocused image still delivers better results compared to the at-focus image.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We have empirically showed that the pixelwise cell-background classification yields considerably better results when the local phase as obtained in [7] is used instead of the defocused image. Nevertheless, the defocused image still delivers better results compared to the at-focus image.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Like its 1D counterpart, it is computed in practice by convolving the signal with a band-pass quadrature filter yielding the local phase and local energy of the input. In [7], a link between the physical phase and the local phase was established using the monogenic signal. According to [7], it is possible to use the monogenic signal framework to approximate the solution of equation (1) under two conditions: First, the derivative image, i.e.…”
Section: Monogenic Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…[21]). We recently outlined a possible mathematical connection, based on filter theory, between the two fields in a separate paper [4]. The advantages of our low-pass filter approach, compared with the phase recovery method of Paganin et al, are that it significantly reduces low-frequency noise associated with conventional phase recovery, and it also provides local orientation information which can be used to improve our algorithm.…”
Section: Cell Boundary Segmentationmentioning
confidence: 99%